2015
DOI: 10.1136/bjsports-2015-094664
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict a poor outcome 5–8 years after the diagnosis of patellofemoral pain: a multicentre observational analysis

Abstract: More than half of participants with PFP reported an unfavourable recovery 5-8 years after recruitment, but did not have radiographic knee OA. Longer PFP duration and worse AKPS score at baseline predict poor PFP prognosis. Education of health practitioners and the general public will provide patients with more realistic expectations regarding prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(156 citation statements)
references
References 51 publications
0
147
2
7
Order By: Relevance
“…With the incidence of PFP reported to be high4 and symptoms persisting despite evidence based interventions,8 further investigation is warranted to understand variables that are associated with PFP development and subsequently deliver evidence based preventative strategies. In 1992, Van Mechelen et al presented a theoretical model described as the ‘sequence of prevention’ for sports injury (see figure 1) to guide injury prevention development 9.…”
Section: Introductionmentioning
confidence: 99%
“…With the incidence of PFP reported to be high4 and symptoms persisting despite evidence based interventions,8 further investigation is warranted to understand variables that are associated with PFP development and subsequently deliver evidence based preventative strategies. In 1992, Van Mechelen et al presented a theoretical model described as the ‘sequence of prevention’ for sports injury (see figure 1) to guide injury prevention development 9.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to what has previously been published, with longer symptom duration being a strong predictor for persistent symptoms in patients with PFP. 2,9 However, the low response rate at the 1-year follow-up in the adolescent group may have caused a selection bias, as the young patients who completed the follow-up reported less pain at baseline and had a higher BMI. This may indicate that the relatively "better" adolescent patients were more likely to complete the follow-up questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prognostic paper indicated that nearly 50% of people with PFP are likely to benefit from traditional physiotherapy in the longer term 2. However, 57% report unfavourable outcomes 5–8 years after being enrolled in a traditional physiotherapy clinical trial, indicating a need for alternative approaches in these individuals 2…”
Section: But Is This Current Focus On Traditional Physiotherapy Optimentioning
confidence: 99%